Triple Fortification of Coconut Milk Chocolate Drinks with Iron, Iodine, and Vitamin A: A Novel Approach to Nutritional Intervention in Resource-Limited Settings - Yakum, Kelly Ndombow; Ariahu, Charles Chukwuma; Abuengmoh, Peter; Terhemba, Nancy Seember; Joyceline, Maboh; Igoli, John Ogbaji (Indonesian Association of Food Technologists, 2025)
This study investigated the production and quality evaluation of fortified and non-fortified coconut milk chocolate drinks with varying sugar and cocoa powder levels. The goal was to reduce post-harvest losses of locally available coconut fruits and cocoa beans by processing them into nutritious drinks. These drinks could serve as a vehicle for micronutrient fortification and thus, help to reduce protein energy malnutrition and micronutrient deficiency that are prevalent amongst children and pregnant mothers in sub-Saharan African countries. All raw materials for the production of drinks were processed using standard good manufacturer and good hygienic practices (GMP and GHP). Chocolate drinks were formulated as: PCCNF (plain coconut milk chocolate non-fortified), PCCF (plain coconut milk chocolate fortified), SCCNF (sweetened coconut milk chocolate non-fortified), and SCCF (sweetened coconut milk chocolate fortified) drinks. Drinks were subjected to triple fortification using KI, FeSO4, and retinol palmitate as recommended by world food fortification programs. All formulations underwent proximate, vitamin, and mineral quality analyses using standard methods. Cocoa powder and the addition of fortificants led to a statistically significant increase (P<0.05) in the proximate composition, particularly in protein and carbohydrate of 3.4-4.0 and 4.8-5.6 g/100 g, respectively. Fortification with KI, FeSO4 and retinol palmitate increased potassium (150-264 mg/100 g), iron level spanned (2.9-3.4 mg/100 g), iodine (0.16-0.38 mg/100 g) and pro vitamin A (1.7-2.5 mg/100 g of drinks as seen in PCCF and SCCF (fortified drinks) compared to non-fortified versions (PCCNF and SCCNF). The study concluded that these drinks were suitable vehicles for micronutrient (iodine, iron, and provitamin A) fortification and protein-energy malnutrition intervention programs.